2020
DOI: 10.1111/jocs.14519
|View full text |Cite
|
Sign up to set email alerts
|

Cardioplegic storage solution: Is it the guardian of saphenous vein graft endothelium?

Abstract: Introduction: Despite their suboptimal long-term patency, saphenous vein grafts are the most widely used conduits to achieve complete revascularization during coronary artery bypass grafting (CABG). Although vein storage critically impairs endothelial integrity, contradictory data concerning optimal storage solutions exist.The aim of this study is to explore any in vitro impact of cardioplegic solutions and temperature on vein grafts endothelial integrity during their storage. Materials and Methods:A single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a recent study, Papakonstantinou et al compared a high potassium, crystalloid cardioplegia solution to AHB for SVG preservation in an ex vivo study with human SVGs. They reported that the cardioplegia solution resulted in significantly better endothelial preservation as measured via immunohistochemistry (see above for study details) [20].…”
Section: Preservation Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Papakonstantinou et al compared a high potassium, crystalloid cardioplegia solution to AHB for SVG preservation in an ex vivo study with human SVGs. They reported that the cardioplegia solution resulted in significantly better endothelial preservation as measured via immunohistochemistry (see above for study details) [20].…”
Section: Preservation Solutionsmentioning
confidence: 99%
“…For instance, Papakonstantinou et al compared the storage of 160 SVG segments from 40 consecutive patients in AHB to crystalloid cardioplegia at both cold (58C) and room temperature (20-258C) and evaluated endothelial integrity via immunohistochemistry. On a Likert-type scale of 1 (worst) to 5 (best), endothelial integrity was significantly better after storage in cardioplegic solution irrespective of temperature (58C: 2.83 AE 0.15 vs. 2.23 AE 0.16; P ¼ 0.0022; 20-258C: 3.10 AE 0.13 vs. 2.0 AE 0.15; P < 0.0001)[20]. Furthermore, in a retrospective, nonrandomized, observational analysis of 1828 patients and 4343 SVG from the PREVENT IV trial, Harskamp and colleagues reported that AHB was associated with higher VGF at 1 year as compared to buffered saline in both patient-level (odds ratio,Fouquet et al demonstrated that AHB had significantly lower rates of graft thrombosis at 6 weeks in an in vivo rat model as compared to the buffered solution L-glutathione, L-ascorbic acid, L-arginine and D-glucose (GALA) (22% vs. 83.3%; P ¼ 0.04) [22].…”
mentioning
confidence: 99%